Heparin-Bonded Expanded Polytetrafluorethylene Grafts in Hemodialysis Access. Issue 1 (March 2016) - Olsha, Oded; Goldin, Ilya; Shemesh, David
When options for autologous arteriovenous (AV) fistulas have been fully exhausted, AV grafts continue to play an important role in access creation for hemodialysis, offering long-term hemodialysis access that is a better alternative to central vein catheters. The drawbacks of AV grafts are their poor patency, infection and higher cost. Their main advantages are that they are widely available, are easy to create, and mature early. In the context of the "Fistula First" initiative, many patients with low quality veins suffer from fistula failure and non-maturation resulting in prolonged catheter days that would otherwise be prevented by initial creation of an AV graft. Endeavors to improve graft patency include administration of pharmacological agents, changing graft configuration, altering graft biology, and altering the graft surface. In this review, the current status of heparin-bonded AV grafts for hemodialysis is discussed.